Health disparities in Europe’s ageing population: the role of social network - Jenny Olofsson; Mojgan Padyab; Gunnar Malmberg (Global Health Action, 2018)
Background: Previous research suggests that the social network may play very different roles in relation to health in countries with differing welfare regimes. Objective: The study aimed to assess the interplay between social network, socioeconomic position, and self-rated health (SRH) in European countries. Methods: The study used cross-sectional data on individuals aged 50+ from the fourth wave of the Survey of Health, Ageing and Retirement in Europe (SHARE) and includes data from 16 countries. The outcome is poor SRH. All analyses are adjusted for age and stratified by gender. Results: Low satisfaction with the social network was associated with poor SRH among women in all country groups, but predicted poor SRH among males in West/Central and Eastern Europe only. The results from the multivariable analysis showed an increased likelihood of poor SRH among those with relatively lower education, as well as among those with low satisfaction with the social network (women from all country groups and men from Western/Central and Eastern Europe). However, the results from interaction analysis show that poor SRH for those with lower relative position in educational level was greater among those with higher satisfaction with the social network among male and female participants from Northern Europe. The health of individuals who are highly satisfied with their social network is more associated with socioeconomic status in Northern Europe. Conclusions: This study highlights the significance of social network and socioeconomic gradients in health among the elderly in Europe.